1993
DOI: 10.1083/jcb.123.1.245
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of putative divalent cation sites in the alpha 4 subunit of the integrin VLA-4: distinct effects on adhesion to CS1/fibronectin, VCAM-1, and invasin.

Abstract: Abstract. To investigate the functional significance of putative integrin divalent cation binding sites, several mutated 0/4 subunit cDNAs were constructed. Mutants contained the conservative substitution of Glu for Asp or Asn at the third position in each of three putative divalent cation sites. Transfection of wild-type or mutated ~ into K562 cells yielded comparable expression levels and immunoprecipitation profiles. However, for all three ~ mutants, adhesion to CS1/fibronectin was greatly diminished in eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
62
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(68 citation statements)
references
References 83 publications
6
62
0
Order By: Relevance
“…Each putative cationbinding N-terminal repeat lacks a potential coordinating residue at the most C-terminal position of the cation-binding loop (26,27). One possible model is that a residue from a ligand may complete metal coordination within one of these domains to stabilize ligand binding (28), although data regarding substitution mutations in this region are inconsistent with this proposition (29).…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…Each putative cationbinding N-terminal repeat lacks a potential coordinating residue at the most C-terminal position of the cation-binding loop (26,27). One possible model is that a residue from a ligand may complete metal coordination within one of these domains to stabilize ligand binding (28), although data regarding substitution mutations in this region are inconsistent with this proposition (29).…”
mentioning
confidence: 60%
“…K562 cells were grown in RPMI 1640 (Irvine Scientific) containing 10% FCS 2 (Sigma), penicillin, and streptomycin. K562 transfectants expressing wild type ␣ 4 integrin (KA4), three derivatives harboring ␣ 4 mutations (N283E, D346E, and D408E), or vector with no insert (KpF) were as described (29). Stably transfected K562 cells were grown in media supplemented with 400 g/ml G418 (Life Technologies, Inc.).…”
Section: Bacterial Strains Plasmids and Bacterial And Eukaryotic Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Recent studies have revealed that the ligand binding activity of integrins can be regulated by factors acting either from outside the cell or from the cell interior. These regulatory factors include temperature, 15 extracellular divalent cations, 21 integrin cytoplasmic domains, 33 and interaction with intracellular signal transduction molecules such as calreticulin, 34 serine/threonine kinases and phosphatases, 35 and members of the small GTPase family including R-Ras 36 and Rho A. 37 Especially, inside-out signaling has a critical role in integrin activation by propagating conformational changes from the cytoplasmic domains of integrins to the extracellular binding sites in response to intracellular signaling events.…”
Section: Discussionmentioning
confidence: 99%
“…The recent discovery of certain anti-␤1 antibodies, which can dramatically stimulate various ␤1 integrin functions, has made it possible to analyze the functional regulation of ␤1 integrins. 15,17,21 In the present study, we have utilized the stimulatory anti-␤1 monoclonal antibody (mAb) TS2/16 to evaluate constitutive activity of ␤1 integrins on multiple HCC cell lines. As a result, ␤1 integrins showed a wide range of constitutive activities in different HCC cell types.…”
mentioning
confidence: 99%